2019
DOI: 10.1186/s11671-019-2945-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Proapoptotic Effects of Water Dispersed Complexes of 4-Thiazolidinone-Based Chemotherapeutics with a PEG-Containing Polymeric Nanocarrier

Abstract: Aim To study whether water formulation of the complex of 4-thiazolidinone derivatives with a PEG-containing polymeric nanocarrier enhances their pro-apoptotic action towards rat glioma C6 cells. Methods Mechanisms of antineoplastic effects of 4-thiazolidinone derivatives were investigated in vitro with rat glioma C6 cells. Cell nativity, cell cycling pattern, and Annexin V expression were evaluated and DNA damage was estimated by DNA comet analysis. A novel water-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…So, overall in vitro studies concluded that compound 22 is a highly active compound against human melanoma cells with a less pronounced effect against carcinoma and leukemia cells [78]. Further, extending the above work, Kobylinska et al [79] investigated the pro-apoptotic effect of compound 22 and its other analog 23 (Figure 6) conjugated with PEG nanocarrier in the glioma C6 cells of the rat. To study the antineoplastic mechanisms of the conjugate system, studies like cell cycling pattern, Annexin V expression, Cell nativity, and DNA damage were performed.…”
Section: Anti-cancer Potential Of Di-substituted Thiazolidine-4-ones ...mentioning
confidence: 89%
See 1 more Smart Citation
“…So, overall in vitro studies concluded that compound 22 is a highly active compound against human melanoma cells with a less pronounced effect against carcinoma and leukemia cells [78]. Further, extending the above work, Kobylinska et al [79] investigated the pro-apoptotic effect of compound 22 and its other analog 23 (Figure 6) conjugated with PEG nanocarrier in the glioma C6 cells of the rat. To study the antineoplastic mechanisms of the conjugate system, studies like cell cycling pattern, Annexin V expression, Cell nativity, and DNA damage were performed.…”
Section: Anti-cancer Potential Of Di-substituted Thiazolidine-4-ones ...mentioning
confidence: 89%
“…Conjugates of both drugs showed enhanced toxicity (LES 3288 and LES 3833) at doses of 0.1 and 0.5 μM compared to free drugs, however, at higher concentrations (1.0 μM) only LES 3288 retained higher toxicity compared to the free drug. Furthermore, DNA comet analysis in glioma C6 cells documented breaks in the nuclear DNA (single strand) without intercalation in the DNA of the tested cells [79]. Skora et al [80] synthesized another series, comprising thiazolidine-4-one conjugated with an indole ring, and subsequently in-vitro screened them for their cytotoxic and cytostatic activity against four cancer cell lines, namely epithelial colorectal adenocarcinoma (CACO-2) cells, lung carcinoma (A549), human fibroblasts (BJ), and neuroblastoma (SH-SY5Y).…”
Section: Anti-cancer Potential Of Di-substituted Thiazolidine-4-ones ...mentioning
confidence: 96%
“…The values determined for the molecular weight parameters of poly(VEP-co-GMA)-graft-PEG are = = 90 kDa, = 165 kDa, and = / = 1.83. Aqueous dispersions of the polymer poly(VEP-co-GMA)-graft-PEG and its complexes with drugs (Dox and Les-3833) were prepared according to the following procedure [7,14]. Firstly, the polymer and the drug were dissolved in DMSO, and then the solutions were transferred into water.…”
Section: Methodsmentioning
confidence: 99%
“…Micelles of comb-like PEG-containing polymers revealed themselves as effective universal carriers of drugs [7,14]. They reliably bind various hydrophilic and hydrophobic antitumor drugs, protect them against biological damages, provide their targeted delivery and high therapeutic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the antitumor mechanisms of these derivatives can be associated with their affinity to c-Jun NH(2)-terminal kinase (JNK) stimulating phosphatase-1 (JSP-1), cyclin-dependent kinases (CDKs), tyrosine kinase, tumor necrosis factor alpha (TNFα), vascular endothelial growth factors, and P-glycoprotein [14][15][16]. We have shown that the 4-thiazolidinone derivative Les-3833 induced the accumulation of tumor cells in the G1-G0 phase, increased the ratio of Annexin Vpositive cells, and increased the amount of pro-apoptotic cleaved caspase-3 in treated cells [17].…”
Section: Introductionmentioning
confidence: 99%